The Implications of Climate Variability on the Livelihood of Local Communities of Melamchi Municipality - Thapa, Sahista; Bhandari, Anil (The Batuk, 2024)
Climate change is humanity's most serious concern, with far-reaching and severe consequences for people, ecosystem services, and the environment. The study aims to evaluate the implications of climate variability on the livelihood of local communities of Melamchi municipality. The study collected primary data through focus groups, interviews, and observations and analyzed 31 years of precipitation and temperature data. The study assessed participatory vulnerability to climate change using indicators of exposure, sensitivity and adaptive capacity. Analysis of precipitation data showed decreasing annual rainfall trends at Dubachaur and Baunepati stations, while Sarmathang station showed an increasing trend. The maximum average annual temperature has shown a rising trend in all three stations. The RAI analysis showed that 2009 had the highest negative value, with an RAI of -4.87, classified as extremely dry from the rainfall data collected from the Baunepati station. Respondents reported severe climate change impacts on livelihoods, including increased temperatures, shifting rainfall, drought, water shortages, and invasive species. The study recommends urgently enhancing local climate adaptation efforts by integrating considerations of water security, food systems, and disaster risk reduction into development planning.